Association between Parents' Nativity Status and Influenza Vaccination Rates among Children - Vasil Yasenov; Michael Hotard; Duncan Lawrence; Jens Hainmueller (Institute of Labor Economics (IZA), 2021)
Previous research has documented lower vaccination rates among ethnic and racial minorities as well as foreign-born people, thus raising concerns about health inequities during pandemics. We analyzed influenza vaccination rates among children with US-born parents and those with at least one immigrant parent. We found that children with immigrant parents have higher odds of receiving the influenza vaccination even after controlling for socio-demographic characteristics.
Keywords: I12; I14; I18; 330; influenza vaccine; immigration; mixed-status families